Eksplorasi Fitur Edpuzzle Sebagai Media Pembelajaran Interaktif Bagi Guru Di SMP Rama Sejahtera - Rahmadani, Amalia; Usman, Musawwir; Annam, Syarful; Fatkhulloh, Shoffan; Sangkala, Nur Rahmah (Fakultas Tarbiyah dan Ilmu Keguruan UIN Syekh Wasil Kediri, 2025)
This community service program was implemented at Rama Sejahtera Junior High School in Makassar with the aim of facilitating teachers' digital literacy and pedagogical competencies through the use of Edpuzzle as an interactive learning medium. The community service activities used the Participatory Action Research method, which included observation, execution, and evaluation with a focus on introducing the main features of Edpuzzle and its application in learning practices. Teachers were trained to create interactive learning videos equipped with questions and notes that encourage student engagement. The results of the activity showed an increase in teachers' ability to develop teaching media and enthusiasm to apply it in the classroom. This program supports the digital transformation of education through innovative and engaging learning.